2023
DOI: 10.1556/1326.2022.01069
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneously measure the concentrations of busulfan and phenytoin in human plasma using an HPLC-MS/MS method: Application to the TDM for children underwent hematological stem cell transplantation

Abstract: In this work, a simple and rapid high performance liquid chromatography tandem mass spectrometry (HPLC-MS/MS) method was developed and validated to carry out the simultaneous measurement of busulfan (BU) and phenytoin (PHT) in the plasma of children. In this method, plasma sample could be prepared by one-step protein precipitation using 1 mL of methanol/water (1:1, v/v). After centrifugation (14,500 rpm, 5 min, 4 °C), 10 μL of the supernatant was injected into a Hypersil Gold C18 column (150 × 2.1 mm, 5 μm, Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…These parameters are related to clinical outcomes, and pharmacodynamic studies have indicated that the optimal Bu target range depends on the conditioning regimen, age of the HSCT recipient, and the underlying disease. 7 Several analytical methods have been used to measure Bu plasma levels, including gas chromatography coupled with mass spectrometry, [7][8][9] high-performance liquid chromatography (HPLC) coupled with ultraviolet spectroscopy, and fluorescence detection. More recently, methodologies based on liquid chromatography coupled with tandem mass spectrometry (HPLC-MS/MS) have been developed that result in high analytical specificity and sensitivity, significantly shorter turnaround times, and a simplified workflow.…”
Section: Introductionmentioning
confidence: 99%
“…These parameters are related to clinical outcomes, and pharmacodynamic studies have indicated that the optimal Bu target range depends on the conditioning regimen, age of the HSCT recipient, and the underlying disease. 7 Several analytical methods have been used to measure Bu plasma levels, including gas chromatography coupled with mass spectrometry, [7][8][9] high-performance liquid chromatography (HPLC) coupled with ultraviolet spectroscopy, and fluorescence detection. More recently, methodologies based on liquid chromatography coupled with tandem mass spectrometry (HPLC-MS/MS) have been developed that result in high analytical specificity and sensitivity, significantly shorter turnaround times, and a simplified workflow.…”
Section: Introductionmentioning
confidence: 99%